2022
DOI: 10.3389/fphar.2022.1001018
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the network pharmacology and the structure-activity relationship of glycyrrhizic acid and glycyrrhetinic acid

Abstract: Licorice, a herbal product derived from the root of Glycyrrhiza species, has been used as a sweetening agent and traditional herbal medicine for hundreds of years. Glycyrrhizic acid (GL) and glycyrrhetinic acid (GA) are the most important active ingredients in licorice. Both GL and GA have pharmacological effects against tumors, inflammation, viral infection, liver diseases, neurological diseases, and metabolic diseases. However, they also exhibit differences. KEGG analysis indicated that licorice is involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 102 publications
(111 reference statements)
0
6
0
Order By: Relevance
“…The available evidence indicates that licorice has the potential to safeguard the structural integrity of the liver against the toxic effects of cadmium (Cd). The active ingredients in licorice, known as glycyrrhizic acid (GL) and glycyrrhetinic acid (GA), have anti-inflammatory and protective properties that can help protect vital organs including the liver, kidneys, heart, and nerves against infections caused by bacteria or viruses [ 47 ]. The primary phytoconstituents found in licorice, including flavonoids, glycyrrhetic acid, hydroxycoumarins, and beta-sitosterol, have been observed to possess inhibitory effects on the enzymes involved in the generation of free radicals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The available evidence indicates that licorice has the potential to safeguard the structural integrity of the liver against the toxic effects of cadmium (Cd). The active ingredients in licorice, known as glycyrrhizic acid (GL) and glycyrrhetinic acid (GA), have anti-inflammatory and protective properties that can help protect vital organs including the liver, kidneys, heart, and nerves against infections caused by bacteria or viruses [ 47 ]. The primary phytoconstituents found in licorice, including flavonoids, glycyrrhetic acid, hydroxycoumarins, and beta-sitosterol, have been observed to possess inhibitory effects on the enzymes involved in the generation of free radicals.…”
Section: Discussionmentioning
confidence: 99%
“…We propose that Licorice's hepatoprotective effects have been attributed to its active ingredients, including glycyrrhizic acid (GA) and glycyrrhetinic acid (GA), which possess anti-inflammatory and protective properties [ 47 ], flavonoids and glycyrrhetic acid which possess antioxidant activities and isoliquiritigenin which helps in inhibiting tissue lipid peroxidation [ 37 ], in addition, licorice bioactive compounds interact with the binding sites of caspase-3, TNFRSF1A, and TNFRSF1B, counteracting apoptosis and inflammatory processes [ 56 ], moreover, Licorice's capabilities of inhibiting the TNF-α secretion, contribute to its protective effects against glyphosate-induced tissue damage [ 56 ]. Overall, licorice represents a promising natural intervention for ameliorating the toxic effects of glyphosate, offering potential therapeutic strategies for detrimental effect of glyphosate-based pesticide (GBPs), especially because of its affordability due to the extensive cultivation of licorice in the Middle East, Asia, and Europe [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, glycyrrhetinic acid blocks the conversion of cortisol to inactive cortisone by suppressing 11β-hydroxysteroid dehydrogenase (Kim and Kim, 2016). Certain studies presented the selective inhibition of glycyrrhizic acid as it was found that 18α-GA preferentially selectively suppresses 11β-HSD-1, while 18β-GA preferentially inhibits 11β-HSD-2 (Ni et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The various pharmacological activities of GL and its derivatives were summarized, and the structurally modified GL-related derivatives were further developed to make them less cytotoxic and more targeted [ 35 ]. Moreover, the interaction between GL and the envelope protein was revealed to be an effective inhibitor of the SARS-CoV-2 envelope protein at the molecular and structural levels [ 36 ].…”
Section: Anti-sars-cov-2 Activitymentioning
confidence: 99%